Untangling the complexities of larval Antarctic krill overwintering success under climate change - Sylvester, Zephyr T; Veytia, Devi; Bahl, Alexis A; Bahlburg, Dominik; Benkort, Deborah; Bestley, Sophie; Cagdas, Bulut; Cleary, Alison C; Constable, Andrew; Corney, Stuart; Fach, Bettina A; Hellessey, Nicole; et al. (ICES Journal of Marine Science, 2025)
Antarctic krill (Euphausia superba) are integral to Southern Ocean pelagic ecosystems. Winters with extensive sea ice have been linked to high post-larval krill recruitment the following spring, suggesting that sea ice plays a critical role in larval overwinter survival. As the ocean warms and sea ice declines under climate change, understanding the mechanisms linking sea ice and krill recruitment is increasingly urgent. To address this, we developed a qualitative network model (QNM) that integrates evidence-based and hypothesized interactions to explore larval overwinter survival and growth under future climate scenarios in the southwest Atlantic sector. Our model highlights habitat-specific impacts, with substantial declines predicted for the North Antarctic Peninsula continental shelf due to reduced autumn primary productivity and warming. In contrast, survival may improve in open-ocean habitats under cooler scenarios that enhance sea-ice-associated processes, such as food availability and refuge. The inclusion of hypothesized mechanisms, such as sea-ice terraces providing refuge from predation, strengthened these conclusions and highlighted critical uncertainties, including the influence of glacial melt on food web dynamics. These findings demonstrate the value of QNMs in complementing quantitative approaches, offering a framework for identifying critical mechanisms, addressing knowledge gaps, and guiding future field and laboratory studies to improve predictions of krill responses to climate change.
Keywords: Sørishavet; fiskerier; klimaendringer; krill; oseanografi; plankton

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking